Improved Physicochemical Properties of Pork Patty Supplemented with Oil-in-Water Nanoemulsion - Lee, Jiseon (Food Sci Anim Resour, 2020)
This study aimed to investigate the effect of nanoemulsion (NEM) on the physicochemical and sensory characteristics of pork patty to improve texture for elderly members of the population. Hence, we prepared pork patties supplemented with different of liquid materials: water; oil and water; oil, water, and surfactants; and nanoemulsion. The emulsion itself was characterized and the physicochemical properties of the pork patties, including pH, water content, cooking loss, thawing loss, liquid holding capacity, color, and texture, were analyzed. The size of NEM was 165.70±9.32 nm and NEM had high ζ-potential value indicating that it is stable. NEM patties had the lowest cooking and thawing losses, and the highest liquid retention, all of which affected the tenderness of the patties. Color of the patty was also affected by the addition of NEM. The highest lightness and yellowness and the lowest redness were observed (p<0.05). NEM patties had the lowest values for all texture attributes indicating improved tenderness. Our results demonstrate that NEM has positive effects on pork patties and can help to tenderize food products designed for the elderly. With further study, NEM could be a candidate tenderization agent in the meat industry.